Innovative teaching of anthropometric through morphosis dualfunction chair design and build - Sanusi, Aliyah Nur Zafirah; Azmin, Aida Kesuma; Abdullah, Fadzidah; Yusof, Zeenat Begam (Centre of Engineering and Built Environment Education Research (PeKA), 2019)
This research is about innovative teaching methodology and learning process of anthropometric study using “Morphosis Dual-Function Chair Design and Build”. The objectives of the study are to develop their knowledge in anthropometrics and ergonomic study and to familiarise first year architecture students about functional requirement and creative aspects of design. The teaching methodology starts with the brief formulation, brief overview, design critique sessions, product making and presentation. A survey on students’ feedbacks on their learning outcomes was conducted and the findings were analysed to establish students’ understanding of the project’s objectives. In conclusions, both objectives have been achieved. Furthermore, students have also learned about teamwork and construction method.